A Low Cost Matching Motion Estimation Sensor Based on the NIOS II Microprocessor - Diego González; Guillermo Botella; Uwe Meyer-Baese; Carlos García; Concepción Sanz; Manuel Prieto-Matías; Francisco Tirado (Sensors, 2012)
This work presents the implementation of a matching-based motion estimation sensor on a Field Programmable Gate Array (FPGA) and NIOS II microprocessor applying a C to Hardware (C2H) acceleration paradigm. The design, which involves several matching algorithms, is mapped using Very Large Scale Integration (VLSI) technology. These algorithms, as well as the hardware implementation, are presented here together with an extensive analysis of the resources needed and the throughput obtained. The developed low-cost system is practical for real-time throughput and reduced power consumption and is useful in robotic applications, such as tracking, navigation using an unmanned vehicle, or as part of a more complex system.